The Human and Educational Significance of Honesty as an Epistemic and Moral Virtue. Issue 1 (February 2014) - Carr, David
Abstract While honesty is clearly a virtue of some educational as well as moral significance, its virtue‐ethical status is far from clear. In this essay, following some discussion of latter‐day virtue ethics and virtue epistemology, David Carr argues that honesty exhibits key features of both moral and epistemic virtue, and, more precisely, that honesty as a virtue might best be understood as the epistemic component of Aristotelian practical wisdom. In the wake of arguments to be found in Plato's Laws, as well as in those of more modern philosophers such as Jean‐Jacques Rousseau and Iris Murdoch, Carr then traces the main roots of moral dishonesty to various forms of vain and self‐delusive ego attachment. In this light, he argues in the final section of the essay that literature and the arts may provide a powerful educational antidote to such attachment.